Trends in nanoformulations for atopic dermatitis treatment - Ramos Campos, Estefânia Vangelie (2020)
Introduction: Immunological skin dysfunctions trigger the synthesis and release of inflammatory cytokines, which induce recurrent skin inflammation associated with chronic itching, inefficient barrier behavior, and reduced skin hydration. These features characterize a multifactorial chronic inflammatory disease atopic dermatitis (AD). AD therapy includes anti-inflammatory drugs and immunosuppressors as well as non-pharmacological alternatives such as emollients, moisturizers, and lipids (ceramides, phospholipids) for modulating the skin hydration and the barrier repair. However, these treatments are inconvenient with low drug skin penetration and insufficient maintenance on the application site. Areas covered: Nanotechnology-based therapies can be a great strategy to overcome these limitations. Considering the particular skin morphological organization, SC lipid matrix composition, and immunological functions/features related to nanocarriers, this review focuses on recent developments of nanoparticulate systems (polymeric, lipid-based, inorganic) as parent or hybrid systems including their chemical composition, physico-chemical and biopharmaceutical properties, and differential characteristics that evaluate them as new effective drug-delivery systems for AD treatment. Expert opinion: Despite the several innovative formulations, research in nanotechnology-based carriers should address specific aspects such as the use of moisturizers associated to pharmacological therapies, toxicity studies, scale-up production processes and the nanocarrier influence on immunological response. These approaches will help researchers choose the most appropriate nanocarrier system and widen nanomedicine applications and commercialization.